CULTURAL HERITAGE, NATION STATE AND GLOBALIZATION: MUTUAL RELATIONS AND INFLUENCES - Jarutis, Vytautas (Politologija, 2015)
This article aims to reveal the role of political power in the construction of collective identity through the collective memory. Three aspects is seeking to “hook” in the theoretical level: the determined trends of globalised current time, the national state as a homogeneous “imagined” community and cultural heritage as a historical reality and factor of joining together communities. The analysis uncovers that globalization is a dualistic phenomena. The tendencies could be marked under living conditions today: the ontological anxiety of society, a collective identity crisis, the legal and actual threats to the sovereignty, which may retain the nation state. Nationalism, as the ideological force homogenizing state and society, is strongly actualizing and becomes a “headache” not only for communities but also for the political authorities, who can’t stay away from declaring liberal laissez-faire principle, but must choose one from David Brown’s proposed nationalism strategies of society’s consolidation: ethno-cultural, civic or multicultural. Cultural heritage expressing a symbolic link to the legacy of previous generations must now become not only culturally, but also political and economic resource to the communities and politicians to create the basis for the stability of society and the state. The role of cultural heritage in the international political economy, development of public image models and developing positive relationships with neighbors in the historical context is very relevant today. Reinterpretation of cultural heritage dissonances in academic and public discourses should help to reconstruct the historical oblivion and construct the new formulas of collective identity in the second millennium of Lithuania.